Integrated Reporting Disclosure and Firm Value: The Moderating Role of Audit Tenure in ASEAN-5 Countries - Maulana, Ghifari Robby; Hakim, Tito IM. Rahman; Muhammad, Erfan; Rohma, Frida Fanani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2025)
This study investigates the effect of integrated reporting disclosure (IRD) on firm value, with audit tenure as a moderating variable. The sample consists of mining and property companies listed in ASEAN-5 capital markets, yielding 363 firm-year observations between 2021 and 2023 through purposive sampling. Using panel data regression, the findings show no significant relationship between IRD and firm value. Moreover, audit tenure negatively moderates this relationship, suggesting that extended auditor tenure weakens the potential benefits of integrated reporting. This negative moderating effect implies that prolonged auditorclient relationships may compromise auditor independence, signal governance concerns to market participants, and reduce the credibility of voluntary disclosure initiatives